Gait Velocity and Joint Power Generation After Stroke: Contribution of Strength and Balance. (October 2019) - Mentiplay, Benjamin F.; Williams, Gavin; Tan, Dawn; Adair, Brooke; Pua, Yong-Hao; Bok, Chek Wai; Bower, Kelly J.; Cole, Michael H.; Ng, Yee Sien; Lim, Lek Syn; Clark, Ross A.
Abstract : Objective: The aim of the study was to assess the degree to which isometric strength of multiple lower limb muscle groups and balance is associated with gait velocity and joint power generation during gait after stroke. Design: Sixty-three participants in a multisite, multinational, cross-sectional, observational study underwent assessment of gait velocity (10-m walk test), standing balance (computerized posturography), and isometric strength (hand-held dynamometry). Twenty-seven participants had joint power generation assessed (three-dimensional gait analysis). Bivariate associations were examined using Spearman's correlations. Regression models with partial F tests were used to compare the contribution to gait between measures. Results: Although all muscle groups demonstrated significant associations with gait velocity (ρ = 0.40–0.72), partial F tests identified that ankle plantar flexor and hip flexor strength made the largest contribution to gait velocity. Ankle plantar flexor strength also had strong associations with habitual and fast-paced ankle power generation (ρ = 0.65 and 0.75). Balance had significant associations with habitual and fast gait velocity (ρ = −0.57 and −0.53), with partial F tests showing that the contribution was independent of strength. Conclusions: Ankle plantar flexor and hip flexor strength had the largest contribution to gait velocity. Future research may wish to refocus strength assessment and treatment to target the ankle plantar flexors and hip flexors. To Claim CME Credits: Complete the self-assessment activity and evaluation online at http://www.physiatry.org/JournalCME CME Objectives: Upon completion of this article, the reader should be able to: (1) Differentiate the contribution that lower limb strength of each muscle group has on gait velocity after stroke; (2) Appraise the relationship between isometric strength and joint power generation during gait; and (3) Interpret the contribution of both strength and balance to gait after stroke. Level: Advanced Accreditation: The Association of Academic Physiatrists is accredited by the Accreditation Council for Continuing Medical Education to provide continuing medical education for physicians. The Association of Academic Physiatrists designates this Journal-based CME activity for a maximum of 1.0 AMA PRA Category 1 Credit(s) TM . Physicians should only claim credit commensurate with the extent of their participation in the activity. Abstract : Supplemental digital content is available in the text.